British Airways v Commission: Always Aim for the Sky. (8th February 2018) - Ortiz Blanco, Luis; Villiers, Sam
Abstract: The Court of Justice of the EU, dismissing the appeal of British Airways, held that the General Court was correct in ruling that it cannot grant an annulment that goes beyond that sought by the applicant, even if the General Court has of its own motion found that there is a public policy defect which vitiates the decision in its entirety.